Economic and social effectiveness of carbon pricing schemes to meet Brazilian NDC targets. (14th January 2022) - Wills, William; La Rovere, Emilio Lebre; Grottera, Carolina; Naspolini, Giovanna Ferrazzo; Le Treut, Gaëlle; Ghersi, Frédéric; Lefèvre, Julien; Dubeux, Carolina Burle Schmidt
ABSTRACT: Curbing GHG emissions while preserving economic growth is one of the main challenges that developing countries are facing to meet the Paris Agreement commitments. Brazil's NDC target aims to reduce economy-wide absolute levels of GHG emissions by 37% in 2025 and 43% in 2030, compared to 2005 emissions. In this paper, we compare command-and-control and carbon pricing policies to induce the Brazilian economy to meet its NDC targets. We focus on analysing synergies and trade-offs in macroeconomic and social development, captured by economic growth and income distribution while reducing GHG emissions. By integrating a series of sectoral models and a computable general equilibrium (CGE) model, we develop and run different policy scenarios that simulate a set of carbon pricing schemes in Brazil. Our analysis shows that NDC implementation in Brazil under carbon pricing policies allows the country to meet its targets and improve economic and social indicators compared to a command-and-control policy. With about the same GHG emissions up to 2030, important macroeconomic and social co-benefits can be achieved under a carbon pricing policy in Brazil, allowing for reduced welfare losses against business-as-usual trends. Key policy insights: Carbon pricing policies are more cost-effective to meet NDC targets in Brazil up to 2030, resulting in higher GDP and household income, in comparison to other individual policy instruments, including command-and-control and subsidies to investments. A carbon price of about 10 USD/tCO2e, combined importantly with deforestation rates under control, would allow Brazil to meet its NDC targets. Recycling carbon pricing revenues can help soften the burden on the labour market and protect low-income households from welfare losses.